If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -1(3x + -6) + 2(4x + 5) + -1x = 0 Reorder the terms: 11 + -1(-6 + 3x) + 2(4x + 5) + -1x = 0 11 + (-6 * -1 + 3x * -1) + 2(4x + 5) + -1x = 0 11 + (6 + -3x) + 2(4x + 5) + -1x = 0 Reorder the terms: 11 + 6 + -3x + 2(5 + 4x) + -1x = 0 11 + 6 + -3x + (5 * 2 + 4x * 2) + -1x = 0 11 + 6 + -3x + (10 + 8x) + -1x = 0 Reorder the terms: 11 + 6 + 10 + -3x + 8x + -1x = 0 Combine like terms: 11 + 6 = 17 17 + 10 + -3x + 8x + -1x = 0 Combine like terms: 17 + 10 = 27 27 + -3x + 8x + -1x = 0 Combine like terms: -3x + 8x = 5x 27 + 5x + -1x = 0 Combine like terms: 5x + -1x = 4x 27 + 4x = 0 Solving 27 + 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 4x = 0 + -27 Combine like terms: 27 + -27 = 0 0 + 4x = 0 + -27 4x = 0 + -27 Combine like terms: 0 + -27 = -27 4x = -27 Divide each side by '4'. x = -6.75 Simplifying x = -6.75
| A=zv+z | | 9-3x-5x=81 | | 7h+5=8+6h | | 0=4s^4-17s^2+4 | | 2+(4p+1s)=5s+2p | | (2x+4)(2x+4)-2(2x+4)+1=0 | | -7-2x+6x=-39 | | A=yt+y | | -7(n-6)=98 | | n-1.3n+1.8=1.5n-1.8 | | 4x^2+32x-60=0 | | -7x-(-7-3x)=-9 | | 6=x+x-6 | | -7h+4=16-8h | | 3p-16p=7+2(-8p-3) | | 3s^2-21s-180=0 | | -2h^2+11h+21=21 | | -(8x+2)=-(1+2x) | | 2y+5y=7 | | (5x+1)(5x+1)-12(5x+1)+36=0 | | 1-3x=2x+18 | | -5(x+4)=-8x-22 | | -6+t=-4 | | -3(x-2)=6-3y | | 2x+c=11c | | x=9-(x-5) | | 7-6x-7x=-149 | | 5h-30=8h | | 5(3-3-3t)=30 | | -(2x+3)=3x-1 | | (4x-9)+8(2x+3)-7x=0 | | 4.4t-2.9=-1.7+3.2 |